Fatores associados às faltas dos professores de escola pública: evidências para as escolas estaduais paulistas - Honda, Lucas Ozeki (2020)
This dissertation intends to analyze the main factors that lead a public school teacher to skip classes. Through a base of absences provided by São Paulo State Department of Human Resources, it was found that some characteristics related to the teachers, the schools where they teach and the students explain their absenteeism. The results suggest that the gender, age and experience of these teachers, besides which grade they teach and how many schools they work in are relevant to understand this. The size of the school and whether it has poor infrastructure are also important factors. Finally, the student's family income and the student interest in school also help to understand teacher’s absenteeism.